How pea fractions with different protein composition and purity can substitute WPI in heat-set gels. (November 2021) - Kornet, Remco; Penris, Simone; Venema, Paul; van der Goot, Atze Jan; Meinders, Marcel B.J.; van der Linden, Erik
Abstract: In this study we explored the gelling behaviour of a pea protein concentrate (PPC), an albumin-fraction (ALB-F) and a globulin-rich fraction (GLB-RF), in comparison with and as substitute for whey protein isolate (WPI), by small oscillatory and large amplitude oscillatory shear (SAOS and LAOS) rheology. It was found that PPC formed the firmest gels (defined as highest elastic modulus), but this gel was not as firm as a pure WPI gel. The ALB-F formed the weakest gel due to its low protein purity. For a better view on the albumin gelling behaviour, ALB-F was further diafiltrated and the albumin-enriched fraction was labelled ALB-RF. It turned out that albumins formed firmer gels per mass unit of protein than globulins. Also, the energy dissipation ratios – a measure for the plasticity of the gel – were determined as a function of strain. The ALB-RF gel showed an increase in plastic response at larger strains compared to the GLB-RF gel (40% and 10% strain, respectively). ALB-F, PPC and GLB-RF were also examined on their ability to substitute WPI in heat-set gels. It was found that ALB-F/WPI mixtures formed firm gels and were least sensitive to changes in pH and ionic strength. It also appeared that disulphide bonding plays a more important role in the ALB-F/WPI mixtures upon heat-set gelation compared to the PPC/WPI and GLB-RF/WPI mixtures. The use of pea fractions as a substitute for WPI, particularly the ALB-F, could improve the resource efficiency of pea as an ingredient source. Graphical abstract: Image 1 Highlights: Pea fractions with globulins, albumins and a mixture were obtained by aqueous fractionation. Pea albumins formed firmer and more ductile gels than pea globulins. The pea fractions could partially substitute whey protein isolate (WPI) in heat-set gels. WPI with the albumin fraction formed the firmest gels at a range of pH and ionic strengths. Disulphide bonding played an important role in the WPI – albumin fraction mixture.